2003
DOI: 10.5014/ajot.57.3.284
|View full text |Cite
|
Sign up to set email alerts
|

Pencil Grips, Legibility, and Speed of Fourth-Graders’ Writing in Cursive

Abstract: Ninety-nine of the students used one of four pencil grips including the dynamic tripod (38 students), the dynamic quadrupod (18), the lateral tripod (22), and the lateral quadrupod (21). One student used the four-finger pencil grip and one used the interdigital pencil grip. Mean cursive writing speeds were similar for all pencil grips except for the interdigital grasp. Speeds obtained were slower than recently published fourth-grade speeds ranging from a mean of 29.45 to 34.75 letters per minute. CONCLUSION. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
2
6

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 8 publications
(8 reference statements)
4
22
2
6
Order By: Relevance
“…Other research has found similar results (Dennis & Swinth, 2001;Koziatek & Powell, 2003;Schwellnus et al, 2012), which further supports the need to determine whether these grasp patterns can be treated as kinetically equivalent. Note.…”
Section: Distribution Of Grasp Patternssupporting
confidence: 67%
See 2 more Smart Citations
“…Other research has found similar results (Dennis & Swinth, 2001;Koziatek & Powell, 2003;Schwellnus et al, 2012), which further supports the need to determine whether these grasp patterns can be treated as kinetically equivalent. Note.…”
Section: Distribution Of Grasp Patternssupporting
confidence: 67%
“…Therapists and teachers commonly recommend that children, especially those with handwriting difficulties, use the DT pencil grasp (Schneck & Henderson, 1990). Three other pencil grasp patterns-namely, the dynamic quadrupod (DQ), the lateral tripod (LT), and the lateral quadrupod (LQ) pencil grasps-are suggested to be mature grasps that are functional in terms of speed or legibility for writing (Dennis & Swinth, 2001;Koziatek & Powell, 2003). The prevalence of each of these grasp patterns in children is comparable to that of the DT grasp (Koziatek & Powell, 2003;Schwellnus et al, 2012).…”
Section: Pencil Grasp Debatementioning
confidence: 99%
See 1 more Smart Citation
“…Esse dado é sugestivo de que crianças brasileiras estão sendo estimuladas a usar o lápis mais precocemente, o que precisa ser melhor investigado. Na literatura, a prevalência da trípode dinâmica, padrão considerado ergonomicamente mais estável, varia de 33 a 67% em crianças acima de 7 anos de idade e adultos 24 . Considerando o reteste a análise dos itens quantitativos da ACOORDEM indica estabilidade temporal, já que 78% dos itens apresentaram boa consistência.…”
Section: Discussionunclassified
“…These research findings were investigated and describes in term of legibility and speed, see [4,5]. However, the scarcity of valid and reliable handwriting evaluation tools, the complexity in the scoring tools and the long processing time by the evaluator who needs to judge the writing product for each of the legibility criteria, limit the application of standardized assessments in the evaluation of handwriting difficulties in clinical and classroom setting [2].…”
Section: Evaluation Of Handwriting Difficultiesmentioning
confidence: 99%